1991
DOI: 10.1128/mcb.11.4.1996
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of simian virus 40 large-T antigen and p53 protein by protein phosphatase 2A: inhibition by small-t antigen.

Abstract: Simian virus 40 (SV40) large-T antigen and the cellular protein p53 were phosphorylated in vivo by growing cells in the presence of 32pi. The large-T/p53 complex was isolated by immunoprecipitation and used as a substrate for protein phosphatase 2A (PP2A) consisting of the catalytic subunit (C) and the two regulatory subunits, A and B. Three different purified forms of PP2A, including free C, the AC form, and the ABC form, could readily dephosphorylate both proteins. With both large-T and p53, the C subunit wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 50 publications
(43 reference statements)
2
102
0
Order By: Relevance
“…Similar observations have been made by others (Sturzbecher et al, 1987). Of additional interest is the finding that the SV40 small t antigen may promote phosphorylation of p53 by blocking protein phosphatase 2A-dependent dephosphorylation of p53 (Scheidtmann et al, 1991b). Taken (Meisner & Czech, 1991 Nuclear protein phosphorylation and growth control Answers to these questions will undoubtedly provide a better understanding about key areas of growth control such as differentiation, development and cellular transformation.…”
Section: _4supporting
confidence: 54%
See 1 more Smart Citation
“…Similar observations have been made by others (Sturzbecher et al, 1987). Of additional interest is the finding that the SV40 small t antigen may promote phosphorylation of p53 by blocking protein phosphatase 2A-dependent dephosphorylation of p53 (Scheidtmann et al, 1991b). Taken (Meisner & Czech, 1991 Nuclear protein phosphorylation and growth control Answers to these questions will undoubtedly provide a better understanding about key areas of growth control such as differentiation, development and cellular transformation.…”
Section: _4supporting
confidence: 54%
“…Concomitant activation of cdkl and PP2A at G1/S could therefore switch T antigen into an active replicating protein in a cell-cycle-dependent manner, thus allowing exploitation of the cell's replication machinery during S phase. It is also possible that the small t antigen of SV40, which down-regulates the activity of PP2A towards T antigen at the inhibitory phosphorylation sites (Yang et al, 1991;Scheidtmann et al, 1991b), is necessary to maintain T antigen in an inactive replication state until its activation at an appropriate point in the cycle. Prior to S phase, T antigen may be employed in other function(s) such as transcription or tumour suppressor protein binding.…”
Section: The Large T Antigen Of Sv40mentioning
confidence: 99%
“…At the p53 N-terminus, there are 10 serine/threonine residues (Ser-6, -9, -15, -20, -33, -37, -46, and , PP2A (Scheidtmann et al, 1991), PP5 (Zuo et al, 1998), Wip1 and Cdc14 (Fiscella et al, 1997;Li et al, 2000), can dephosphorylate p53, there is no definitive assignment of the concrete phosphatase responsible for dephosphorylating the specific serine/threonine sites until recently. Long et al The inducibility of the Tet-on system.…”
Section: Dephosphorylation Of P53 Displays Strong Impact On Its Functmentioning
confidence: 99%
“…Thus, p53 is responsible for regulating of cell death through Bax/Bcl-2 imbalances. Furthermore, p53 is a phosphoprotein, it has been shown that in vivo phosphorylated p53 can be dephosphorylated in vitro by PP2A (Scheidtmann et al, 1991). Besides, it has been found that PP2A inhibitor can induce hyperphosphorylation of p53 and increased apoptosis (Yan et al, 1997;Milczarek et al, 1999).…”
Section: Introductionmentioning
confidence: 99%